Analytical methods and formulation factors to enhance protein stability in solution - Jeong, Seong Hoon (Archives of pharmacal research, 2012)
Development of stable protein formulations needs intimate knowledge of the proteins’ physicochemical properties. More specifically, understanding the mechanisms of protein degradation is important in designing and evaluating protein formulations. This review describes briefly the different types of interactions of the major protein degradation pathways. The analytical methods to detect protein degradation are included, along with generalized strategies to suppress protein instability with relevant excipients. With an appreciation of the current practices for stable formulations, the development process will be facilitated in a more efficient way.